Pregnancy, delivery, and postpartum period in infantile liver failure syndrome type 2 due to variants in NBAS - Bianca Peters; Felix Wiemers; Dominic Lenz; Stefan Kölker; Georg F. Hoffmann; Siegmund Köhler; Christian Staufner (JIMD Reports, 2023)
Abstract Biallelic pathogenic variants in the neuroblastoma amplified sequence (NBAS) gene affecting the Sec39 domain are associated with a predominant hepatic phenotype named infantile liver failure syndrome type 2 (ILFS2). Individuals are at risk of developing life‐threatening acute liver failure episodes, most likely triggered by febrile infections. Pregnancy, delivery, and the postpartum period are well known triggers of decompensation in different inherited metabolic diseases and therefore entail a potential risk also for individuals with ILFS2. We studied pregnancy, birth, and postpartum period in a woman with ILFS2 (homozygous for the NBAS variant c.2708 T > G, p.(Leu903Arg)). During two pregnancies there were no complications associated with the underlying genetic condition. Two healthy boys were born by cesarean section. To reduce the risk of fever and febrile infections, we avoided prolonged labor, epidural analgesia, and breastfeeding. Maternal body temperature and liver function were closely monitored. In case of elevated body temperature, antipyretic treatment (acetaminophen, metamizole) was given without delay. Alanine and aspartate aminotransferases as well as liver function remained normal throughout the observation period. Hence, pregnancy and childbirth are feasible in women with ILFS2 under careful monitoring.